Carbon nanotube based composites for electricity storage in supercapacitors - Zhang, Shengwen (2010)
In the context of fossil-fuel shortage and climate change, the production, conversion, storage and distribution of energy have become the focus of today's world. Supercapacitors, with their unique energy and power density specifications, cover the application gap between batteries and conventional capacitors and hence making valuable contributions in energy storage and distribution.